Guanidiniocarbonyl pyrrole (GCP) conjugated PAMAM-G2, a highly efficient vector for gene delivery: the importance of DNA condensation. Issue 84 (3rd October 2016) - Samanta, Krishnananda; Jana, Poulami; Bäcker, Sandra; Knauer, Shirley; Schmuck, Carsten
Abstract : A novel hybrid compound1 efficiently shuttles genetic material into HeLa cells at concentrations as low as 0.6 μM, whereas the parent compound PAMAM-G2 is ineffective even at 200 μM. Abstract : A novel hybrid compound1 efficiently shuttles genetic material into HeLa cells at concentrations as low as 0.6 μM, whereas the parent compound PAMAM-G2 is ineffective even at 200 μM. The high efficiency of1 stems from its capabiliy to form highly condensed ligand–DNA polyplexes. Its binding affinity is actually lower than for the parent dendrimer. Compound1 is even 200 times more effective and less cytotoxic than PEI, the current gold standard in gene transfection with cationic polymers.